Measuring On-shelf Availability of FMCG Products - Grubor, Aleksandar; Milićević, Nikola M (Industrija, 2015)
Technological development and the process of globalization influence the increase of customers’ awareness. In these circumstances they are becoming more demanding, expecting retailers to offer them the right product at the right time and at the right place. The result is one of the basic tasks of retailers, which reflects in providing an adequate level of product availability in retail stores. In order to prevent the stock-out situation, special attention should be dedicated to its identification and measurement. These operations are very important for establishing and implementing other various measures for increasing product availability and thus sales and competitiveness of retail companies. In this regard, besides theoretical considerations of product availability, we presented the basic methods for its measurement. Also, by using the sample of six Fast Moving Consumer goods categories, we applied the method based on the analysis of POS data. In addition to identifying the out-of-stock rates, we confirmed the results of other studies that product availability varies among different categories and retail stores.